FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN BIDAN DESA DALAM PELAYANAN PEMBERIAN TABLET BESI PADA IBU HAMIL DI KABUPATEN PEKALONGAN TAHUN 2013 - Maslahatul Inayah; Mardi Hartono; Rr. Sri Sedjati; Tri Anonim (LPPM Universitas Pekalongan, 2014)
One of the causes of maternal death in peklongan in 2013 is bleeding. Preliminary studies showed that administration of iron tablets in pregnant women has not been implemented in accordance with the optimal standards of care. This study aims to analyze the factors that influence compliance midwife in service provision of iron tablets to pregnant women in Pekalongan.Quantitative research was conducted with a cross-sectional survey approach. The population is the entire village midwife (366 people). Selection of subjects performed as many 79 people clustered random sampling at the primary care level. Bivariate analysis performed with the Spearman rank test and Pearson-product Moment and multivariat analysis with logistic regression Regression.The result showed that the average age of respondents 32 5,7 years (SD). The average service life of 10 5,8 years (SD). Only 27,8% of respondents who are obedient in the service provision of iron tablets and 44,3% of respondent who have a good knowledge. A total of 48,1% of respondents have a good level of need and 50,6% of respondents who have a good level of confidence in the service provision of iron tablets. A total of 49,4% of respondents have a good perception of supervision and as much as 57% of respondents have a good perception of the award. A total of 55,7% of respondents perceive punishment important in service provision of iron tablets to pregnant women. The results of bivariate analysis showed that knowledge (p=0,003), supervision (p=0,0001) , award (p=0,001), punishment (p=0,004) related to compliance midwife. There jointly influence between supervision (p=0,002; Exp.B=30,0) , award (p=0,031; Exp.B=5,4) , knowledge(p=0,220 ; Exp.B=2,3) , punishment hukuman (p=0,294 ; Exp=2,1), for compliance midwife in service provision of iron tablets to pregnant women in Pekalongan.Supervision is the most influental factor to adherence midwife in service provision of iron tablets to pregnant women. It is recommended to conduct regular supervison directly to the field and improve coaching tiered periodically to the village midwife.